The importance of the communicative approach in teaching speech acts in English - Xamrayeva , Xakima (The Lingua Spectrum, 2024)
This thesis discusses the importance of the communicative approach in teaching speech acts in English, to strengthen communication between students in the educational process and to create opportunities for practical use of the language. Communicative approach focuses on preparing students for real-life situations rather than learning language only as grammar and vocabulary. This approach allows students to develop speaking skills, express their thoughts and establish effective communication with other communication participants. Also, this methodology encourages cooperation and teamwork among students, thus enhancing students’ creative thinking and problem-solving skills.